Influences on the Development of Inquiry-Based Practices Among Preservice Teachers. Issue 2 (17th February 2017) - Cian, Heidi; Dsouza, Nikeetha; Lyons, Renee; Cook, Michelle
ABSTRACT: As preservice teachers (PSTs) acquire experiences in their field, they confront difficulties implementing what they learned during their teacher education programs. The successful or unsuccessful outcomes of the challenges they face influence the development of their identity as teachers. One practice that many PSTs are encouraged to implement during their preservice experience is inquiry-based instruction. However, even if students begin their fieldwork with a basic understanding of inquiry, the realities of the classroom and their incongruence with what the PST came to expect during university coursework may dissuade them from committing to an inquiry-based approach. We interact with PSTs in a single science teaching university methods course to collect data using an inquiry-specific observation protocol as well as from interviews and written reflections. Through case study research framed within situated cognitive learning theory, we find that elements of PSTs' experience have a profound influence on their views of inquiry and of themselves as teachers in an inquiry-based classroom. We identify themes of translating theory to practice, perceiving inquiry as additional work, and utilizing resources.